Toxicity assessment of DMSO extracts of environmental aged beached plastics using human cell lines - Florane Le Bihanic; Bettie Cormier; Emilie Dassié; Sophie Lecomte; Justine Receveur; Stéphane Le Floch; Jérôme Cachot; Bénédicte Morin (Ecotoxicology and Environmental Safety)
Plastic products contain complex mixtures of chemical compounds that are incorporated into polymers to improve material properties. Besides the intentional chemical additives, other compounds including residual monomers and non-intentionnaly added substances (NIAS) as well as sorbed pollutants are usually also present in aged plastic. Since most of these substances are only loosely bound to the polymer via non-covalently interactions, i.e., van der Waals forces, they may leach to the surrounding environment. Although there is increasing knowledge about toxicity of weathered plastic to aquatic organisms, only little is known about how plastic associated chemicals affect human health. Seafood consumption is one of the routes of human exposure to microplastics. The aim of this study was to evaluate the ability of naturally aged plastic associated chemicals to induce harmful effects to human health via the consumption of MP-contaminated seafood. Human colorectal adenocarcinoma Caco-2 and human hepatocyte carcinoma HepG2 cells were selected as model of the colon and liver cells respectively. They are known for their high capacity to metabolize organic contaminants. Both cell lines were exposed to DMSO extracts of different plastics to investigate the effects of chemicals on cell viability, oxidative stress induction and genotoxicity. In addition, the estrogenic effects of DMSO-extracts were evaluated using an estrogen-dependent reporter gene assay in T47D-Kbluc human breast cancer cells. Chemical profiles of the DMSO extracts were polymer-dependent, with polyvinyl chloride (PVC) highly contaminated with metals while polypropylene (PP) contained the lowest concentration of metals. Organic pollutants, including polycyclic aromatic hydrocarbons, were mainly found in PVC, high density polyethylene (HDPE) and PP extracts, whereas other extracted plastics had less (PP) to no organic contamination (polyethylene terephthalate PET). PVC was the most toxic plastic inducing cytotoxicity for both cell lines. DNA damage was observed for Caco-2 cells exposure to HDPE, PVC and nylon. Reactive oxygen species were induced only with nylon extracts in intestinal cells. No toxicity was observed for PP and PET and none of the tested plastics had any estrogenic effect. Our results demonstrate that some environmental aged plastic material released a variety of known and unknown chemical compounds some of which are toxic in vitro and contribute to the knowledge on adverse human health effects of plastics.